Operationalizing Energy Democracy: Challenges and Opportunities in Vermont's Renewable Energy Transformation - Stephens, Jennie C.; Burke, Matthew J.; Gibian, Brock; Jordi, Elie; Watts, Richard (Frontiers in Communication, 2018)
The state of Vermont provides a unique case of a United States jurisdiction intentionally promoting multiple ideals of energy democracy as the state commits to transitioning toward renewable energy. Collaboration among stakeholders state-wide has resulted in innovations that advance energy democracy goals, yet limited examples of community ownership has resulted in strong community opposition to some renewable projects. This small state has adopted a comprehensive energy plan with a goal of achieving 90% renewables in all sectors (electricity, heating and transportation) by 2050. A diverse set of Vermont stakeholders are aligned toward achieving this goal, and an innovative, networked effort seeks to establish a creative and inclusive environment for individuals, communities and organizations to benefit. A collaborative culture has created a protected environment where innovation and experimentation is supported and encouraged. Yet tension surrounding siting of some wind and solar projects has led to strong community opposition. This case highlights challenges and opportunities of operationalizing energy democracy. Recognizing that local community and public ownership is critical to distributing the economic and political power associated with renewable energy, Vermont demonstrates how controversy can emerge despite a culture of collaboration and experimentation.